Digital Operational Resilience in the Banking Sector and Its Contribution to Financial System Stability - Heru Kurniawan; Deo Renaldi Saputra; Hafidz Hanafiah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the structural impact of digital operational resilience within the banking sector on macroeconomic financial system stability utilizing a quantitative, non experimental research design. Applying Generalized Method of Moments estimation to a longitudinal dataset of systemically important commercial banks across emerging and developed economies, the inquiry evaluates how technical engineering practices, infrastructure redundancy, and technology risk disclosure quality insulate the financial architecture from systemic shocks. The empirical results indicate that highly integrated digital platforms and decentralized software topologies significantly reduce institutional insolvency risk, thereby preserving aggregate market liquidity during acute technical stress events. However, rapid financial digitalization introduces complex risk transmission channels and systemic spillovers that can bypass traditional capital adequacy buffers if left unregulated. The findings underscore the critical role of macroprudential policy tools, central bank electronic currencies, and digital sovereignty regulations in governing cross border digital transactions. This research expands classical financial stability theory by establishing a comprehensive empirical framework that links micro level institutional robustness to macro level financial system equilibrium.